Analysis of Risk Control Accounts Receivable on Unbillable Melia Bali Indonesia in Nusa Dua - N K R Ariantini; I N Sugiarta; Istiarto Istiarto (Journal of Applied Sciences in Accounting, Finance, and Tax, 2018)
Credit sales policy was an attempt by management Melia Bali Indonesia to increase the volume of profit. Credit sales will generate the receivable, the high amount of receivables led to an increased risk of bad debts at the end of the period. Therefore, it is necessary to control credit risks that can be controlled uncollectible. This study aims to (1) know the condition of the loan, (2) determine the management of the receivables, (3) determine the risk of the receivables at the Melia Bali Indonesia. This study uses data in the form of aging schedule and credit sales summary Melia Bali Indonesia. The analysis is used to analyze the condition of the loan is 5C analysis, the analysis used to analyze the management of accounts receivable is Receivable Turn Over, Days of Receivable, Arrears ratio, and the ratio of Billing. The analysis is used to analyze the risk of accounts receivable is a trend analysis. The results showed a lack of effective lending rules because only two of the five principles of 5C met. In the management of accounts receivable are only a few that falls below the standard set hotel. Risks faced by the hotel tends to decrease and below the average of companies that demonstrate uncontrolled credit risk. Overall control of receivables conducted by Melia Bali Indonesia can be said is not maximized. In the management of accounts receivable are only a few that falls below the standard set hotel. Risks faced by the hotel tends to decrease and below the average of companies that demonstrate uncontrolled credit risk. Overall control of receivables conducted by Melia Bali Indonesia can be said is not maximized. In the management of accounts receivable are only a few that falls below the standard set hotel. Risks faced by the hotel tends to decrease and below the average of companies that demonstrate uncontrolled credit risk. Overall control of receivables conducted by Melia Bali Indonesia can be said is not maximized.